Determination of the absolute configuration of gliomasolide D through total syntheses of the C-17 epimers - Seetharamsingh, B.; Ganesh, Routholla; Reddy, D. Srinivasa (Journal of Natural Products, 2017)
The absolute configuration at C-17, the carbon bearing the distal hydroxy group of the 14-membered natural product gliomasolide D, was assigned as R by comparison of C-13 NMR shifts and specific rotation values of the epimers at C-17. The first total synthesis of gliomasolide D along with its C-17 epimer, regioselective macrocyclization (18 membered vs 14 membered), and regioselective Wacker oxidation are highlights of the present work.